Taxing Childcare: Effects on Childcare Choices, Family Labor Supply, and Children - Gathmann, Christina; Sass, Björn (Journal of Labor Economics, 2018)
Previous studies report a range of estimates for the response of female labor supply and childcare attendance to childcare prices. We shed new light on these questions using a policy reform that raises the price of public day care. After the reform, children are 8 percentage points less likely to attend public day care, which implies a compensated price elasticity of −0.6. There is little labor supply response in the full sample, although there are declines for vulnerable subgroups. Spillover effects on older siblings and fertility decisions show that the policy affects the whole household, not just targeted family members.